2022
DOI: 10.1200/po.21.00463
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Neoadjuvant Chemotherapy Response and 5-Year Outcome in Patients With Estrogen Receptor–Positive, Human Epidermal Growth Factor Receptor 2–Negative Breast Tumors That Reclassify as Basal-Type by the 80-Gene Signature

Abstract: PURPOSE The 80-gene molecular subtyping signature (80-GS) reclassifies a proportion of immunohistochemistry (IHC)-defined luminal breast cancers (estrogen receptor–positive [ER+], human epidermal growth factor receptor 2–negative [HER2–]) as Basal-Type. We report the association of 80-GS reclassification with neoadjuvant treatment response and 5-year outcome in patients with breast cancer. METHODS Neoadjuvant Breast Registry Symphony Trial (NBRST; NCT01479101 ) is an observational, prospective study that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Furthermore, other assays such as BluePrint and MammaPrint were investigated 23 , 24 with similar outcomes, but a poor concordance of only 59% comparing BluePrint and PAM50 was shown 25 . Several smaller studies have shown a significant association between the Recurrence Score (RS) and pCR following NACT 26 30 while a few have not 31 , 32 , and a significant association with pCR after NACT was shown for a high RS (OR 4.87, 95% CI 2.01, 1.82) in 898 ER-positive and HER2-negative breast cancer patients 10 .…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, other assays such as BluePrint and MammaPrint were investigated 23 , 24 with similar outcomes, but a poor concordance of only 59% comparing BluePrint and PAM50 was shown 25 . Several smaller studies have shown a significant association between the Recurrence Score (RS) and pCR following NACT 26 30 while a few have not 31 , 32 , and a significant association with pCR after NACT was shown for a high RS (OR 4.87, 95% CI 2.01, 1.82) in 898 ER-positive and HER2-negative breast cancer patients 10 .…”
Section: Discussionmentioning
confidence: 98%
“…Biologic diversity of HER2+ breast cancers has been described using BluePrint and other genomic assays such as PAM50, which consistently show a population of IHC/FISHdefined HER2+ patients with functionally activated Luminal or Basal pathways. 8,[23][24][25] Importantly, within this cHER2 NBRST cohort, BluePrint further classified 44.4% as either Luminal-Type or Basal-Type. BluePrint was performed on preoperative core biopsies, suggesting that this genomic diversity is not evident by IHC/FISH methods.…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormones and their receptors are critical in the development and progression of the breast and prostate cancers ( Hayes et al, 2022 ). BC progression can be promoted by sustained exposure of estrogen and at least 70% of BCs are identified as estrogen receptor (ER)-positive luminal type whose development and growth are dependent on the estrogen-activated ERα ( Whitworth et al, 2022 ). In prostate cancer, tumorigenesis is promoted by androgen through androgen receptor (AR)-mediated gene-expression ( Nanda et al, 2020 ).…”
Section: Roles Of Trna-derived Small Rnas In Different Diseasesmentioning
confidence: 99%